Blending flipped classroom with inquiry learning as an innovative approach to teaching science - Wahida, Mariyam; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Technology has always played a crucial role in science teaching and learning. Research studies shows pedagogical approaches employed need to be more interactive in engaging students in order for students to successfully help to achieve mastery of fundamental concepts. Meanwhile the pedagogy used in the delivery of content needs to meet the demands of the 21st century. As students at all levels interact with digital technology on a regular basis, digital media can be used to reform education from conventional to learning based on technology. Flipped classroom has gained popularity as an innovative approach to be utilized in teaching science at different levels. Flipped classroom accompanied with inquiry learning involves a paradigm shift is utilizing digital technology and online resources to leverage learning where more time can be spend interacting with students and engaging students in active learning. Inquiry learning has been a strongly supported strategy to teach science as for many years it has helped students to acquire science concepts, skills and abilities to understand scientific inquiry and encourage active engagement of students. Advancement in the technology and the passion, young generation have for digital media can be used to reform education from conventional to technology-based education by blending flipped classroom with inquiry learning in science teaching and learning. Aided with technological tools, flipped classroom with inquiry can transform the learning environment from a teacher-centered to learner-centered, make learning more interactive and supportive for science teaching in the 21st century.